Waveguide QED with Mössbauer nuclei - Andrejic, Petar; Lohse, Leon Merten; Pálffy, Adriana (Physical Review A, 2024)
Thin-film nanostructures with embedded Mössbauer nuclei have been successfully used for x-ray quantum optical applications with hard x-rays coupling in grazing incidence. Here we address theoretically an alternative geometry, in which hard x rays are coupled in forward incidence (front coupling), setting the stage for waveguide QED with nuclear x-ray resonances. We present in a self-contained manner a general model based on the Green's function formalism of the field-nucleus interaction in one-dimensional waveguides and show that it combines aspects of both nuclear forward scattering, visible as dynamical beating in the spatiotemporal response, and the resonance structure from grazing incidence, visible in the spectrum of guided modes. The interference of multiple modes is shown to play an important role, resulting in beats with wavelengths on the order of tens of micrometers, on the scale of practical photolithography. This allows for the design of special sample geometries to explore the resonant response or microstriped waveguides, opening a toolbox of geometrical design for hard x-ray quantum optics.
CRIS-Team Scopus Importer:2024-06-14